Does Perceived Stress Mediate the Association Between Workplace Bullying and Long-Term Sickness Absence?. Issue 6 (June 2016) - Grynderup, Matias Br⊘dsgaard; Nabe-Nielsen, Kirsten; Lange, Theis; Conway, Paul Maurice; Bonde, Jens Peter; Francioli, Laura; Garde, Anne Helene; Kaerlev, Linda; Rugulies, Reiner; Vammen, Marianne Agergaard; H⊘gh, Annie; Hansen, Åse Marie
Abstract : Objective: To examine if perceived stress mediated the association between workplace bullying and subsequent long-term sickness absence. Methods: The PRISME cohort was established in 2007 and re-examined in 2009. Questionnaire data about workplace bullying and perceived stress were obtained from 4114 individuals. Participants were followed in registers on long-term sickness absence (≥30 consecutive days of sickness absence). Results: Workplace bullying was associated with subsequent sickness absence (odds ratio [OR] = 2.05; 95% confidence interval [CI]: 1.57 to 2.65) and concurrent high perceived stress levels (OR = 2.34; 95% CI: 1.86 to 2.96). A high perceived stress level was also associated with subsequent sickness absence (OR = 1.33; 95% CI: 1.13 to 1.56). Perceived stress explained 13% (95% CI: 6 to 23%) of the total association between bullying and sickness absence. Conclusions: The association between workplace bullying and subsequent long-term sickness absence may be partially mediated by perceived stress.